The recommended interval for cervical cancer screening: Victorian women's attitudes to an extended interval. (25th February 2015) - Scalzo, Katherine; Mullins, Robyn
Abstract Aim: To determine Victorian women's knowledge of the recommended Pap test screening interval and support for extending the interval from two years to three years, in light of possible changes to the National Cervical Screening Program. Methods: A random sample of 2, 360 women aged 18–69 was interviewed by telephone about their knowledge of the recommended interval, their willingness to change to three‐yearly screening if recommended and reasons for their preference. Results: More than 91% of women were aware of the current screening recommendation and nearly half (48.7%) indicated they would be willing to change to three‐yearly screening. Women were less likely to support the change if they were up‐to‐date with screening (45.7%, p<0.01), of low socioeconomic status (43.8%, p<0.01) or aged 50–69 (44.4%, p<0.01). Dislike of having a Pap test was reason for some women to want a longer interval, but most needed to be confident a longer interval was safe to be willing to change. Conclusions and implications: A longer interval between screening tests would readily be accepted by some women, but others will need to be persuaded of the safety of a new recommendation. The current interval is widely known and a clear communication strategy will be needed explain the change and its rationale.